If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + -1) = 3(x + -2) Reorder the terms: 5(-1 + x) = 3(x + -2) (-1 * 5 + x * 5) = 3(x + -2) (-5 + 5x) = 3(x + -2) Reorder the terms: -5 + 5x = 3(-2 + x) -5 + 5x = (-2 * 3 + x * 3) -5 + 5x = (-6 + 3x) Solving -5 + 5x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + 5x + -3x = -6 + 3x + -3x Combine like terms: 5x + -3x = 2x -5 + 2x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 -5 + 2x = -6 + 0 -5 + 2x = -6 Add '5' to each side of the equation. -5 + 5 + 2x = -6 + 5 Combine like terms: -5 + 5 = 0 0 + 2x = -6 + 5 2x = -6 + 5 Combine like terms: -6 + 5 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5
| (13x+1)+(9x+3)=180 | | 3+4x=-1+2x | | 12x+6=7x+6 | | 3+4x=2x+-1 | | 4.9a=49 | | 5*365= | | -5x-7=-6-3 | | 2(x+3)5-x-12=2 | | (4/12)(9/12)=x | | x-17=82 | | d-14=12 | | 4(x+4)=5+4x | | 4x+3=2x+-1 | | x+32=93 | | 2y-2=3y+3 | | x/3=x-22 | | 7y+3+=12y-2 | | 5x^2-7x+12=3 | | z+24=76 | | 1,000+25n-300=740+32n-320 | | 20+.05m=15+.25m | | 2x+12=4(x+3)-2x | | 35(6/10) | | 11=35-2 | | 219-6x=30x+15 | | (16/10)=(24/x) | | 4w+3w-6w=w-15+2w-3w | | 14/2=12/x | | (18/12)=(3x/16) | | -1=32-16+t | | 10(x+3)=8x-14 | | 3x=183 |